Lionfish (Pterois miles and Pterois volitans) influence on the artisanal fishing value chain, Southern Caribbean of Costa Rica - Laguna Cruz, Max (2019)
Introduction: The “Lionfish” are actually two invasive species that occur in several parts of the world, and their effect on local fisheries needs study. Objective: To analyze the influence of these fish on the artisanal fisheries value chain in the Southern Caribbean of Costa Rica. Methods: We surveyed 181 fishermen, restaurant owners and resident consumers, and made counts during fishing operations. Results: Lionfish do not reach consumers in significant numbers, mainly because there is not enough initial input of raw material to compete against established species. Conclusion: we recommend a campaign for the consumption of Lionfish in Costa Rica.